The Intensity of Playing Online Games and Their Implications for the Implementation of Islamic Values Among PAI Students of the University of Muhammadiyah Bandung - Ratu Fitria Nova; Supala; Ibrohim, Iim; Mukhlishah; Hernawati; Muhtadin (Yayasan Mentari Madani, 2025)
The advancement of digital technology has significantly influenced students’ lifestyles, particularly the increasing intensity of online gaming. For students in the Islamic Education (PAI) Program at University Muhammadiyah Bandung, who are expected to exemplify Islamic value, the habit of playing online games may affect religious discipline, time management, and spiritual awareness. This study aims to determine: (1) the level of online gaming intensity; (2) the level of Islamic values implementation; and (3) the influence of online gaming intensity on the implementation of Islamic values among students in the Islamic Education. This research employed a quantitative descriptive approach with a sample 80 students selected through simple random sampling. Data collection techniques included observation, questionnaires, and documentation, while data were analyzed using descriptive statistics, simple linear regression, and the coefficient of determination. The result showed that both online gaming intensity (82%) and the implementation of Islamic values (84%) were categorized as high. Regression analysis indicated a significant influence of gaming intensity on the implementation of Islamic values (Sig. 0,017 < 0,05), with an effect size 7%. These findings emphasize the importance of self-regulation, time management, and continuous Islamic character development to ensure that digital engagement does not undermine students’ religious commitment.